Development and preliminary evidence of the psychometric properties of the GNE myopathy functional activity scale. (April 2018) - Mayhew, Jill; Bonner, Nicola; Arbuckle, Rob; Turnbull, Alice; Bowden, Alexandra; Skrinar, Alison
Aim: GNE myopathy, a rare, severe, progressive myopathy, presents with lower extremity distal muscle weakness. The GNE myopathy functional activity scale (GNEM-FAS) evaluates the impact of GNE myopathy on functioning in adults. This paper presents the psychometric validation of the GNEM-FAS.Patients & methods: Validation of the GNEM-FAS was performed using data from a randomized, double-blind, placebo-controlled Phase-II study (n = 46).Results: Domain score distributions were acceptable. Moderate inter-item correlations (typical range, 0.40–0.70), strong item convergent and discriminant validity and high internal consistency reliability (α = 0.88–0.92) supported the instrument structure. Test–retest reliability was strong (ICC range: 0.87–0.95). Scale scores distinguished among subjects with differing disease severity (p < 0.05).Conclusion: This study provides preliminary evidence of the GNEM-FAS as a valid, reliable assessment.